Protocol for a cluster randomised trial evaluating a multifaceted intervention starting preconceptionally—Early Interventions to Support Trajectories for Healthy Life in India (EINSTEIN): a Healthy Life Trajectories Initiative (HeLTI) Study. Issue 2 (16th February 2021) - Kumaran, Kalyanaraman; Krishnaveni, Ghattu V; Suryanarayana, Kumar Gavali; Prasad, Manohar Prabhu; Belavendra, Antonisamy; Atkinson, Stephanie; Balasubramaniam, Ramaswamy; Bandsma, Robert H J; Bhutta, Zulfiqar A; Chandak, Giriraj Ratan; Comelli, Elena M; Davidge, Sandra T; et al.
Abstract : Introduction: The Healthy Life Trajectories Initiative is an international consortium comprising four harmonised but independently powered trials to evaluate whether an integrated intervention starting preconceptionally will reduce non-communicable disease risk in their children. This paper describes the protocol of the India study. Methods and analysis: The study set in rural Mysore will recruit ~6000 married women over the age of 18 years. The village-based cluster randomised design has three arms (preconception, pregnancy and control; 35 villages per arm). The longitudinal multifaceted intervention package will be delivered by community health workers and comprise: (1) measures to optimise nutrition; (2) a group parenting programme integrated with cognitive–behavioral therapy; (3) a lifestyle behaviour change intervention to support women to achieve a diverse diet, exclusive breast feeding for the first 6 months, timely introduction of diverse and nutritious infant weaning foods, and adopt appropriate hygiene measures; and (4) the reduction of environmental pollution focusing on indoor air pollution and toxin avoidance. The primary outcome is adiposity in children at age 5 years, measured by fat mass index. We will report on a host of intermediate and process outcomes. We will collect a range of biospecimens including blood, urine, stool and saliva from the mothers, as well as umbilical cord blood, placenta and specimens from the offspring. An intention-to-treat analysis will be adopted to assess the effect of interventions on outcomes. We will also undertake process and economic evaluations to determine scalability and public health translation. Ethics and dissemination: The study has been approved by the institutional ethics committee of the lead institute. Findings will be published in peer-reviewed journals. We will interact with policy makers at local, national and international agencies to enable translation. We will also share the findings with the participants and local community through community meetings, newsletters and local radio. Trial registration number: ISRCTN20161479, CTRI/2020/12/030134; Pre-results.